PENGARUH KOMBINASI LARUTAN BUAH BINAHONG, KUNYIT, DAUN SUJI TERHADAP TINGKAT KEKONTRASAN JARINGAN BATANG BAYAM (Amaranthus spinosus L) SEBAGAI MEDIA BELAJAR JARINGAN TUMBUHAN - Melda Ayu Priskilia; Rasuane Noor; Hening Widowati (BIOEDUKASI (Jurnal Pendidikan Biologi), 2022)
Observations in this study were about variations in the combination of solutions of  fruit Basella alba Linn, tubers  of Curcuma longa Linn, leaves Dracaena angustifolia as natural alternative dyes, with variations in the order of administration of solutions that produced contrasting preparations of plant tissue preparations of spinach stems (Amaranthus spinosus L). The study aimed to determine the effect of interaction variations from the combination of  Basella alba, Linn fruit solution, tubers of Curcuma longa Linn, Dracaena angustifolia leaves on the level of clarity of plant tissue preparations, variations in the order of giving the best solution can be used as natural alternative dyes and the results of the study can be used as a medium for high school biology learning. This study was presented using qualitative descriptive data processing using 6 treatments with 3 replications with 2 negative control without using dye and positive control using safranin dye. This research was conducted at the Integrated Science Laboratory, Muhammadiyah Metro University. Based on the data analysis, the results showed that the variation in the order of administration of the solution affected the clarity of the preparations. Variations in the order of tubers of Curcuma longa Linn solution,  Basella alba, Linn fruit, Dracaena angustifolia leaves gave the best effect on the clarity of plant tissue in stems of spinach (Amaranthus spinosus L). The results of this study can be used as a medium for learning biology in the form of preserved preparations.Kata kunci: Jaringan tumbuhan, buah binahong, kunyit, daun suji, Pewarna alami